Does inoculation with native rhizobia enhance nitrogen fixation and yield of cowpea through legume-based intercropping in the northern mountainous areas of Vietnam? - Nguyen, Trung Thanh; Atieno, Mary Otieno; Herrmann, Laetitia; Nakasathien, Sutkhet; Sarobol, Ed; Wongkaew, Arunee; Nguyen, Kien Tri; Lesueur, Didier (Cambridge University Press, 2020)
In the Northern mountainous region of Vietnam, cassava–cowpea intercropping system has been widely promoted with support from the local agricultural department. However, cowpea yield is often limited because of a low Biological Nitrogen Fixation (BNF) activity due to its low natural nodulation and lack of available effective Rhizobium products. The aim of this study was to identify the most effective native rhizobia isolate nodulating cowpea with the potential to increase BNF and yield of cowpea. A greenhouse experiment was initially conducted with five treatments: three native rhizobia isolates (CMBP037, CMBP054, and CMBP065); a control (no inoculation and no N application); and N+ (no inoculation, application of N as KNO3). Field inoculations were carried out and the treatments were as follows: a control (no inoculation); CMBP (037+054) – a mixture of strains from Mau Dong; CMBP065 strain from Cat Thinh. CMBP054 and CMBP065 had the highest nodulation in the greenhouse (46.4 and 60.7 nodules plant−1, respectively) and were rated as effective with symbiotic efficiency (SEF) of 54.56 and 55.73%, respectively. In the field, CMBP (037+054) recorded significantly higher nodulation (19.4 nodules plant−1) than the control (11.7 nodules plant−1). CMBP (037+054) also increased cowpea shoot dry weight, shoot N, and yield by 28.6, 4.9, and 10.5%, respectively, compared to the uninoculated control. This effect was slope dependent (statistically significant in moderate and steep slope, not with gentle slope). Besides, the high expansion rate of intercropping with cowpea showed the high adoption level of these agroecological practices by local farmers. This study reveals the potential of native rhizobia inoculation to enhance soil fertility and sustainable agriculture in the Northern mountainous region of Vietnam and proposes enhanced efforts to promote the availability and utilization of effective inoculants for cowpea.